Acupuncture for tension-type headache: a systematic review and meta-analysis of randomized controlled trials - Kang, Wen-lin; Xiao, Xian-jun; Fan, Rong; Zhong, Dong-ling; Li, Yu-xi; She, Jian; Li, Juan; Feng, Yue; Jin, Rong-jiang (Frontiers in Neurology, 2023)
Background Tension-type headache (TTH) is the most common neurologic disease worldwide. Acupuncture is commonly applied to treat TTH, but evidence of acupuncture for TTH is contradictory based on previous meta-analyses. Therefore, we conducted this systematic review and meta-analysis to update the evidence of acupuncture for TTH and aimed to provide a valuable reference for clinical application. Methods We searched 9 electronic databases from their inceptions to July 1, 2022 for randomized controlled trials (RCTs) of acupuncture for TTH. We also manually searched reference lists and relevant websites, and the experts in this field were consulted for possible eligible studies. Two independent reviewers conducted literature screening, data extraction, and risk of bias assessment. The revised Cochrane risk-of-bias tool (ROB 2) was used to assess the risk of bias of included studies. Subgroup analyses were carried out based on frequency of acupuncture, total sessions, treatment duration, needle retention, types of acupuncture and categories of medication. Data synthesis was performed using Review Manager 5.3 and Stata 16. The Grading of Recommendations Assessment, Development and Evaluation Approach (GRADE) was used to evaluate the certainty of evidence of each outcome. Meanwhile, the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) was used to assess the reporting quality of interventions in clinical trials of acupuncture. Results 30 RCTs involving 2,742 participants were included. According to ROB 2, 4 studies were considered as low risk, and the rest studies were some concerns. After treatment, compared with sham acupuncture, acupuncture had greater effect in improvement of responder rate [3 RCTs, RR = 1.30, 95%CI (1.13, 1.50), I2 = 2%, moderate certainty] and headache frequency [5 RCTs, SMD = −0.85, 95%CI (−1.58, −0.12), I2 = 94%, very low certainty]. In contrast to medication, acupuncture was more effective to reduce pain intensity [9 RCTs, SMD = −0.62, 95%CI (−0.86, −0.38), I2 = 63%, low certainty]. Adverse events were evaluated in 16 trials, and no serious event associated with acupuncture occurred. Conclusions Acupuncture may be an effective and safe treatment for TTH patients. Due to low or very low certainty of evidence and high heterogeneity, more rigorous RCTs are needed to verify the effect and safety of acupuncture in the management of TTH.